The value of prostate-specific antigen density for prostate imaging-reporting and data system 3 lesions on multiparametric magnetic resonance imaging: a strategy to avoid unnecessary prostate biopsies - Görtz, Magdalena; Radtke, Jan Philipp; Hatiboglu, Gencay; Schütz, Viktoria; Tosev, Georgi; Güttlein, Maximilian; Leichsenring, Jonas; Stenzinger, Albrecht; Bonekamp, David; Schlemmer, Heinz-Peter; Hohenfellner, Markus; Nyarangi-Dix, Joanne (European urology focus, 2019)
Background - Multiparametric magnetic resonance imaging (mpMRI) has excellent sensitivity in detecting significant prostate cancer (sPC). Nevertheless, uncertainty exists regarding the management of Prostate Imaging-Reporting and Data System (PI-RADS) 3 lesions. - Objective - To investigate whether PI-RADS 3 lesions in combination with clinical parameters, especially prostate-specific antigen density (PSAD), can be used to exclude sPC. - Design, setting, and participants - A total of 455 consecutive biopsy-naïve men underwent MRI-guided transperineal prostate fusion biopsy at our department between 2017 and 2018. We identified 101 patients who had exclusively one or more PI-RADS 3 lesions on mpMRI. sPC was defined as intermediate- and high-risk PC (according to the D’Amico risk classification). - Outcome measures and statistical analysis - Univariate logistic regression analysis was performed to test different clinical factors as predictors of sPC in men with PI-RADS 3 lesions. The probability of sPC prediction was calculated for different PSAD thresholds. - Results and limitations - Among patients with PI-RADS 3 lesions, PSAD was a significant predictor of sPC (p = 0.005). For a PI-RADS score of 3 the probability of excluding sPC was 85% (86/101), which increased to 98% (42/43) when combined with PSAD <0.1 ng/ml/ml. - Conclusions - Inclusion of PSAD < 0.1 ng/ml/ml in the strategy for biopsy-naïve patients with equivocal mpMRI findings would allow a reduction in prostate biopsies in 43% (43/101) of cases at the cost of missing a very small number (2%, 1/43) of intermediate-risk PCs. - Patient summary - At high-volume tertiary care centers with significant experience in prostate multiparametric magnetic resonance imaging, immediate biopsies could be safely omitted for men with lesions with a Prostate Imaging-Reporting and Data System score of 3 and prostate-specific antigen density of PSAD < 0.1 ng/ml/ml. Any decision to omit an immediate biopsy should be associated with close monitoring.